Between the Principled Pragmatism and the Normative Approach: Which Approach the European Union is following in Jordan? - Aleassa, Lina (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to clarify that the European Union (EU) is trapped between its normative approach which seeks to promote the EU idealized values as emphasized by the European Security Strategy of 2003, and its principled pragmatism approach, which makes resilience building the governing rationale of the EU's engagement in the region, as illustrated by the European Union Global Strategy of 2016.This shift following the Arab Spring aimed to reconcile the EU values and interests, yet the study revealed the EU is trapped between these two approaches. Methods: This study is built on a textual analysis of the literature on the EU's external action within the framework of the EU's engagement with Jordan, a partner of the EU, document analysis of their cooperation including their bilateral and multilateral agreements supported by semi- structured interviews with project managers of the 'EU Support to Jordanian Democratic Institutions and Development' along academics, politicians and civil activists from Jordan and the EU. Results: The results of the study showed that with all the crises in the EU Southern Neighborhood, the EU has found itself trapped, where choosing the right path between its values, the normative approach and interest, the pragmatist approach, has been a challenge. Further, it revealed that the EU is incapable of fostering resilience sources including effective governance, social trust and legitimacy. Conclusions: The study suggested scenarios the EU may adopt to reduce the rhetoric-practice gap and reveal the EU's commitment to its values including dropping the selective applicability of conditionality